Sex difference in lipid levels in first-diagnosed drug-naïve depression patients: A case-control and 12-weeks follow-up study. (16th March 2022) - Yang, Rui; Wang, Lu; Cao, Song; Chen, Ming; Wu, Chu-Jun; Silva, Floyd; Shen, Man-Jun; Chen, Jin-Dong; Tang, Mi-Mi; Liu, Bi-Lian
Abstract: Aim: Patients with depression have a high prevalence of developing dyslipidemia. In this study, we aim to investigate the difference of serum lipids, including total cholesterol (TCH), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG), between the depressed patients and healthy controls. Sex differences in lipids and their psychological correlations were also included. Methods: The study included 56 healthy controls (males/females = 26/30) and 110 first-diagnosed drug-naïve outpatients (males/females = 35/75). A total of 42 patients (males/females = 14/28) were followed for 3 months. Results: A significant difference was found in TCH and LDL-C among healthy control and patients. Interestingly, female patients with first-diagnosed, drug-naïve depression had lower atherogenic indices than male patients. After 3 months of antidepressants therapy, female patients exhibited detrimental changes in serum lipids, namely increased TG and atherogenic index. Moreover, correlation analysis showed significant correlations between changes of depression inventory (HAMD and BDI) score and serum lipids (TCH, HDL-C) in depressed patients. Conclusion: We found that dyslipidemia was more common in female patients with depression during therapy with antidepressants. Moreover, the altered serum lipids and atherogenic index might be a hallmark of female patients. Further investigation of sex differences in lipid metabolism of depression is warranted.